Моделирование течения в форсажной камере сгорания авиационного двигателя - Логинов, В. В.; Рублёв, В. И. (НТУ "ХПИ", 2004)
Results of a gas dynamic flow modeling in the swirl-stabilized combustion of the bypass turbofan engine are given in this article. It has been shown that the presented soft ware package can be used for carrying out a computational investigation of gas flow in an afterburner at preliminary design phases
Keywords: летательные аппараты; самолет; потери гидравлические; потери тепловые; диффузор; фронтовое устройство; течение